Traiphumikatha the story of the three planes of existence - Khana Thamng?an Khr?ongk?an Wannakam ??As?ian (Thailand).; ASEAN Committee on Culture and Information ([Bangkok] Khana Kammakan Asian waduai Watthanatham l S arasontet, 1985)
Collection of excerpts, some in old Thai with accompanying modern Thai translations, from Thai body of literature in various genres on three worlds of theravada Buddhism; i.e., world of carnality, world of form, and world of formlessness; roughly corresponding to earth, heaven, and hell.
In Thai; pref. in English.
Errata slip inserted.
Bibliography: p. 294-295.
Keywords: Buddhist cosmology